GABA Measurement in a Neonatal Fragile X Syndrome Mouse Model Using 1H-Magnetic Resonance Spectroscopy and Mass Spectrometry - Reyes, Samantha T.; Mohajeri, Sanaz; Krasinska, Karolina; Guo, Scarlett G.; Gu, Meng; Pisani, Laura; Rosenberg, Jarrett; Spielman, Daniel M.; Chin, Frederick T. (Frontiers in Molecular Neuroscience, 2020)
Fragile X syndrome (FXS) is the leading monogenetic cause of autism spectrum disorder and inherited cause of intellectual disability that affects approximately 1 in 7,000 males and 1 in 11,000 females. In FXS, the Fmr1 gene is silenced and prevents the expression of the fragile X mental retardation protein (FMRP) that directly targets mRNA transcripts of multiple GABAA subunits. Therefore, FMRP loss adversely impacts the neuronal firing of the GABAergic system which creates an imbalance in the excitatory/inhibitory ratio within the brain. Current FXS treatment strategies focus on curing symptoms, such as anxiety or decreased social function. While treating symptoms can be helpful, incorporating non-invasive imaging to evaluate how treatments change the brain’s biology may explain what molecular aberrations are associated with disease pathology. Thus, the GABAergic system is suitable to explore towards developing novel therapeutic strategies for FXS. To understand how the GABAergic system may be affected by this loss-of-function mutation, GABA concentrations were examined within the frontal cortex and thalamus of 5-day-old wild type and Fmr1 knockout mice using both 1H magnetic resonance imaging (1H-MRS) and liquid chromatography-tandem mass spectrometry (LC-MS/MS). Our objective was to develop a reliable scanning method for neonatal mice in vivo and evaluate whether 1H-MRS is suitable to capture regional GABA concentration differences at the front end of critical cortical period where abnormal neurodevelopment that occurs due to FMRP loss is first detected. 1H-MRS quantified GABA concentrations in both frontal cortex and thalamus of wild type and Fmr1 knockout mice. To substantiate the results of our 1H-MRS studies, in vitro LC-MS/MS was also performed on brain homogenates from age-matched mice. We found significant changes in GABA concentration between the frontal cortex and thalamus within each individual mouse from both wild type and Fmr1 knockout mice using 1H-MRS and LC-MS/MS. Significant GABA levels were also detected in these same regions between wild type and Fmr1 knockout mice by LC-MS/MS, validating that FMRP loss directly affects the GABAergic system. Thus, these new findings support the need to develop an effective non-invasive imaging method to monitor novel GABAergic strategies aimed at treating patients with FXS.